Climatic and Ecological Changes in the Subtropical High Andes During the Last 4,500 Years - Mayta, Cesar; Maldonado, Antonio (Frontiers in Earth Science, 2022)
The effects of climate change may be more evident in mountainous areas. In these areas, an increase in temperature and a decrease in precipitation can reduce the amount of snow, which represents a source of water for human consumption and vegetation. To analyze the effects of climate change on vegetation it is possible to examine the climate-vegetation relationship in the past and observe the influence of variation in temperature and precipitation on the dynamics of plant communities. The present work aims to describe the climate-vegetation dynamics of the last 4500 years in the high sub-tropical Andes of Chile (30°S). The paleoclimatic reconstruction was carried out through the analysis of fossil pollen and macroscopic carbon obtained from sediment cores from two high Andean lakes. The dynamic of the vegetation was analyzed taking into account the alpha and beta diversity. The pollen and carbon records showed three contrasting periods during the last 4500 years. From the beginning of the sequences until ~ 1900 years BP, relatively dry climatic conditions are suggested, with a slight trend towards more humid conditions after 2700 years BP. Pollen records from ~ 1900 to ~ 600 years BP suggest wetter conditions than today. Finally, relatively arid conditions have reappeared in the last ~ 600 years. The diversity analysis showed that the climate mainly influences the composition of taxa in the communities (beta diversity) and not the richness (alpha diversity). In periods of dry / wet transition and vice versa, beta diversity changes. On the other hand, richness remains relatively constant throughout the record.